MiR-543/SNTB1 axis modulates immune microenvironment in colorectal cancer - ZHANG Min; LI Min; XIAO Meng (陆军军医大学学报)
Objective‍　‍To investigate the clinical significance of the miR-543/syntrophin beta 1 (SNTB1) axis in colorectal cancer (CRC) and its influence on the tumor immune microenvironment. Methods‍　‍The expression of SNTB1 in CRC tissues was analyzed using public data, such as, The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), and Human Protein Atlas (HPA). Then Kaplan-Meier survival analysis, univariate Cox regression analysis and correlation analysis were performed to evaluate the prognostic value of SNTB1 and its relationship with immune microenvironment in CRC. The targeting relationship between miR-543 and SNTB1 was confirmed through online databases and fluorescence assays in HT-29 cells. For in vitro experiments, after transfecting si-SNTB1, miR-543 mimics and/or SNTB1 overexpression plasmids, HT-29 cells were co-cultured with CD8+ T cells, the expression of miR543 and SNTB1 and the viability and cytotoxicity of CD8+ T cells were assessed with qRT-PCR, Western blotting, flow cytometry, ELISA, and lactate dehydrogenase (LDH) release assay. Results‍　‍Analysis of public databases revealed significantly higher expression of SNTB1 in CRC tissues than normal tissues (P<0.001). The CRC patients with high SNTB1 expression exhibited poorer prognosis when compared with those with low expression level (P<0.05). Moreover, high SNTB1 expression was negatively correlated with immune scores in the tumor microenvironment and immune cell infiltration, especially CD8+ T cells (P<0.05). Furthermore, Knockdown of SNTB1 in HT-29 cells enhanced the cytotoxic activity of CD8+ T cells (P<0.01). Online database and in vitro experiments confirmed that miR-543 targets SNTB1, while the expression of miR-543 was decreased in colorectal cancer (P<0.001). Transfection with the miR-543 mimic inhibited the expression of SNTB1 in HT-29 cells (P<0.001), while overexpressing SNTB1 counteracted the promotion effect of miR-543 mimics on CD8+ T cell-mediated cytotoxicity (P<0.05). Conclusion‍　‍MiR-543 activates CD8+ T cells and enhances their cytotoxicity against HT-29 cells by directly targeting SNTB1.